Front veranda divided by five semi-circular arches - Mumbai Archive Project (Jio Institute, 2024)
The front veranda is divided by five semi-circular arches. Corinthian pillars support the brackets on the first-floor balcony. Over the years, the building has undergone many structural changes. For example, the second floor was added later and was originally not part of the building. The building on the right was also added later and has a staircase leading directly to the first and second floors. This new building has partly obstructed the front view of the façade of the older building.